2014
DOI: 10.1073/pnas.1320451111
|View full text |Cite
|
Sign up to set email alerts
|

Third-party punishment increases cooperation in children through (misaligned) expectations and conditional cooperation

Abstract: The human ability to establish cooperation, even in large groups of genetically unrelated strangers, depends upon the enforcement of cooperation norms. Third-party punishment is one important factor to explain high levels of cooperation among humans, although it is still somewhat disputed whether other animal species also use this mechanism for promoting cooperation. We study the effectiveness of third-party punishment to increase children's cooperative behavior in a large-scale cooperation game. Based on an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 57 publications
4
54
0
2
Order By: Relevance
“…Since this paper studies the development of discrimination between language groups, we excluded 231 children who stated that they speak both languages with their parents from the subsequent analysis. 7 Lifting anonymity in cooperation experiments with children is particularly problematic, because it has been shown that children who belief that they can be sanctioned for non-cooperation significantly increase their cooperation-rates (Lergetporer et al, 2014). This observation may well extend to informal sanctioning behavior outside the laboratory setting.…”
Section: Table 1 About Herementioning
confidence: 99%
“…Since this paper studies the development of discrimination between language groups, we excluded 231 children who stated that they speak both languages with their parents from the subsequent analysis. 7 Lifting anonymity in cooperation experiments with children is particularly problematic, because it has been shown that children who belief that they can be sanctioned for non-cooperation significantly increase their cooperation-rates (Lergetporer et al, 2014). This observation may well extend to informal sanctioning behavior outside the laboratory setting.…”
Section: Table 1 About Herementioning
confidence: 99%
“…Initiated by the seminal work by Fehr and Fischbacher (2004a), a large body of experimental research has shown that even third parties, who are not directly involved in twoparty interactions, frequently impose punishment when they encounter unfair economic interactions in dilemma games (e.g., Fehr and Fischbacher 2004a, Carpenter and Matthews 2012, Kurzban et al 2007, Lergetporer et al 2014. Many scholars have uncovered a number of features of such third-party punishment, especially by using dictator games with third-party punishment.…”
Section: Introductionmentioning
confidence: 99%
“…This study consists of five treatments. In each 1 The literature also suggests that providing third parties an opportunity to reward second-party players likewise does not help cooperation norms to evolve in a dilemma situation (e.g., Sutter et al 2009) 2 The experiment by Lergetporer et al (2014), using children (whose ages were 7 to 11 years old), showed that subjects incorrectly anticipated that third-party punishment was very common and thus believed cooperation would be materially more beneficial, although defection was in fact still the payoff-maximizing action considering the actual frequency of punishment. See McAuliffe et al (2011) for evidence on the prevalence of third-party punishment by young children in a dictator game.…”
Section: Introductionmentioning
confidence: 99%
“…A second set of studies, such as Murnighan and Saxon (1998);Harbaugh et al (2002), have examined bargaining behavior in ultimatum games, and find that younger subjects will make less generous offers which are also more willingly accepted. These results raise the question at what age do pro-social tendencies (Lergetporer et al, 2014) and social preferences (Fehr et al, 2008(Fehr et al, , 1 2013 develop. Our study addresses the question, at what age do people develop strategic sophistication in zero-sum games with mixed minimax strategies?…”
Section: Introductionmentioning
confidence: 97%